Relações entre habilidades metacognitivas, habilidades sociais, planos e saúde mental em cuidadores familiares que assistem idosos dependentes - Isaac, Letícia (2018)
Many people who assist their dependent elderly relatives have trouble finding the time and energy for activities that are important for their mental health. In this study, a model was proposed to indicate skills that may affect a caregiver’s ability to establish plans that are important to their mental health and well-being, such as metacognitive skills (monitoring and self-regulation), social skills, and the ability to establish viable goals. Interviews were conducted with 30 caregivers, including 28 women and 2 men, with an average age of 57.5 years (SD = 11.09), concentrated in socioeconomic classes B and C, and who resided in the interior of the state of São Paulo. The participants responded to the following instruments: open questions about planning adjustments in care routines, Social Skills Inventory for Caregivers of Elderly Family Members, a Life Plans register, Zarit Burden Interview, and Beck Depression Inventory II. The results showed that caregivers own socioemotional wellbeing and the elderly person’s health were constantly monitored by the caregivers. To handle demands related to the caregiving context, about two-thirds of the caregivers enlisted the help of family members, friends, and professionals. However, half of the caregivers reported managing new or unexpected demands on their own, and this was often their only strategy. With respect to their social skills, the caregivers reported having a good repertory of skills, with their greatest strength being affective expression. More than half of the participants reported light to moderate perceptions of burden and depressive symptoms. In terms of their plans for the future, the caregivers mentioned more plans related to health and leisure activities. Eight categories were developed to capture differences in the quality of the plans. Plans for the maintenance of valued activities were most frequently mentioned, followed by plans that were classified as vague, and then viable plans. Scores for each factor of the social skills, burden and depressive symptoms measures were then correlated with the number of plans in each of the eight categories. Assertive Communication skills were positively related with the number of Viable Plans (r = .38, p = .04), the number of Vague Plans was positively related with perceptions of burden involving Emotional Tensions (rho = .39, p =. 03), while the number of Plans being Implemented was negatively related to Emotional Strains (rho = -.41, p = .02). Thus, in consonance with the proposed model, in this study, there is some initial evidence that metacognitive abilities and social skills may be important in the process of constructing viable plans for the future, which, in turn, seem to affect caregivers’ mental health. If researchers continue to find evidence in support of this model, these concepts can be used to develop and evaluate interventions to help caregivers make better use of skills that can improve their ability to construct viable plans, which may contribute to reducing perceptions of burden and the experience of depressive symptoms.